Fuel cells technologies for fuel processing - Shekhawat, Dushyant; Spivey, James J.; Berry, D. A. 1922- (Elsevier, 2011)
This book covers all aspects of fuel processing: fundamental chemistry, different modes of reforming, catalysts, catalyst deactivation, fuel desulfurization, reaction engineering, novel reforming concepts, thermodynamics, heat and mass transfer issues, system design, recent research and development, etc., which makes it one single source of information for scientists and engineers. It serves as an excellent self-instruction book for those new to fuel cells, and as a comprehensive resource for experts in the area of fuel processing. It can be used as a reference book for advanced level university courses in this area. Chapters written by experts in each area Extensive bibliography supporting each chapter Detailed index Up-to-date diagrams and full colourillustrations Associated webpages with links to other relevant material Numerical problems with solutions.
Keywords: Fuel cells.; elektronické knihy; electronic books